Artificial leather and preparation method thereof
By using environmental protection and degradable PHA substrates and non -PHA substrates, combined with auxiliary materials and optimized hierarchical structures, the environment and performance problems of existing synthetic leather in production and use. Good environmental protection and artificial leather.
Patent Information
- Application Number
- CN202310480131.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing synthetic leather consumes a lot of oil during the production process, causing toxic pollution, and the finished product has poor breathability, strong feel, and poor affinity for the skin, which cannot meet the needs of consumers.
Environmental protection and degradable PHA substrates, combined with non -PHA substrates and auxiliary materials, by adjusting the types and proportion of substrate materials, optimizing the hierarchical structure and molding process, and preparing a soft, elastic and good skin -friendly artificial leather.
The full life cycle environment friendship of artificial leather has been realized, and the traditional leather has been avoided by traditional leather to animals and ecology, and at the same time improve the environmental protection and degradability and recycling utilization rate of products.
Smart Images

Figure CN116641241B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of leather, and in particular to artificial leather and a preparation method thereof. Background Art
[0002] Leather is widely used in many modern fields including car interiors, furniture, leather shoes and leather clothing, decoration, etc. Leather usually includes two categories: natural leather and synthetic leather. Due to the condemnation of animal protectionism, natural leather has gradually been replaced by synthetic leather.
[0003] However, the main components of synthetic leather are petroleum-based materials such as polyvinyl chloride (PVC), polyurethane (PU), nylon microfiber, acrylic fiber, spandex, etc., which consume a lot of petroleum in the production process, produce toxic pollution, and the finished products are difficult to compost and degrade in the natural environment. Although it has high chemical stability at room temperature and excellent physical properties such as wear resistance and tear strength, it still has problems such as poor air permeability, hard hand feel, poor affinity to the skin, irritating odor, and even free formaldehyde, which cannot meet the needs of consumers.
[0004] In addition, leather also has antibacterial and anti-mite requirements when in use. Most of the existing antibacterial leathers have poor elasticity. After the leather is squeezed or pressed for a long time, it takes a long time to rebound. This is because a lot of antibacterial and antifungal agents are added during production, impregnation or surface treatment, resulting in a hard feel and poor elasticity, which cannot achieve an ideal and comfortable feel. Summary of the invention
[0005] In order to solve the above-mentioned problems, the present invention provides an artificial leather that is naturally and fully degradable, soft to the touch, elastic, skin-friendly, antibacterial and mildew-proof, waterproof and breathable, and easy to dye. No solvents and adhesives are required during the production process, truly achieving environmental friendliness in the entire production, use, and disposal process.
[0006] A first aspect of the present invention provides an artificial leather.
[0007] Preferably, the artificial leather comprises a base fabric layer, a filling layer, a foaming layer and / or a simulation layer.
[0008] Preferably, the artificial leather comprises a substrate, and the substrate comprises a PHA substrate.
[0009] Preferably, the substrate also includes a non-PHA substrate.
[0010] Further preferably, in the base fabric layer, filling layer, foaming layer and / or simulation layer, the mass ratio of the PHA substrate to the non-PHA substrate is (1-5):1, preferably any value in (2-4):1, for example, 1:1, 1.5:1, 2:1, 2.46:1, 2.5:1, 2.85:1, 2.86:1, 2.88:1, 3:1, 3.09:1, 3.5:1, 4:1, 4.5:1, 5:1.
[0011] Preferably, the PHA comprises a homopolymer or a copolymer of monomers constituting PHA.
[0012] Further preferably, the monomers constituting PHA include, but are not limited to, one, two or more of 2-hydroxypropionic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 3-hydroxyvaleric acid, 3-hydroxypropionic acid, 5-hydroxyvaleric acid, 3-hydroxyhexanoic acid, 3-hydroxyheptanoic acid, 3-hydroxyoctanoic acid or 3-hydroxynonanoic acid, 3-hydroxydecanoic acid, and 3-hydroxydodecanoic acid.
[0013] In a specific embodiment of the present invention, the PHA is selected from one or more of P(HB-LA), P3HP, PHB, P4HB, PHV, PHO, PHN, PHD, PHBV, P34HB, PHBHHp, PHBHHx, P3HB4HB3HV or P3HB4HB5HV.
[0014] In a specific embodiment of the present invention, the PHA is a mixed raw material of P34HB and non-P34HB PHA.
[0015] Preferably, the added mass of P34HB in the PHA is any value between 21% and 79%, preferably any value between 25% and 70%, for example, 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%.
[0016] Preferably, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%, for example, 3%, 5%, 8%, 10%, 12%, 15%, 16%, 20%, 24%, 25%, 30%. Preferably, the non-PHA substrate includes but is not limited to one or more of PLA, PBAT, PPC, PBS, PGA, black tea fiber, soybean protein fiber, mulberry fiber, sugarcane fiber, and bamboo fiber.
[0017] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHB and P34HB, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%, for example, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 4HB in the P34HB is 16%; preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, for example, 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%, in a specific embodiment of the present invention. In the embodiment, the mass ratio of PHB and P34HB in the PHA substrate is 3:2; the non-PHA substrate in the artificial leather is black tea fiber, mulberry fiber and PBS, and the mass ratio of black tea fiber, mulberry fiber and PBS in the non-PHA substrate of the base fabric layer is 4.5:3:10; the mass ratio of black tea fiber, mulberry fiber and PBS in the non-PHA substrate of the filling layer and / or foaming layer is 6:4:13.3; the mass ratio of black tea fiber, mulberry fiber and PBS in the non-PHA substrate of the simulation layer is 3:2:6.7; the mass ratio of PHA substrate and non-PHA substrate in the substrates of the base fabric layer, the filling layer and the foaming layer is 2.86:1; the mass ratio of PHA substrate and non-PHA substrate in the simulation layer is 2.85:1.
[0018] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHBV and P34HB, the molar content of 3HV in the PHBV is any value in the range of 1%-30%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 3HV in the PHBV is 5%, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%. A value, such as 3%, 5%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 4HB in the P34HB is 12%, preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, such as 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%, in a specific embodiment of the present invention, the PHA substrate PHBV
[0019] and P34HB is 1:1; the non-PHA substrate in the artificial leather is soybean protein fiber, PLA and PBAT, and the mass ratio of soybean protein fiber, PLA and PBAT in the non-PHA substrate in the base fabric layer is 4.5:5:8; the mass ratio of soybean protein fiber, PLA and PBAT in the non-PHA substrate in the filling layer and / or foaming layer is 6:6.7:10.7; the mass ratio of soybean protein fiber, PLA and PBAT in the non-PHA substrate in the simulation layer is 3:3.3:5.3; the mass ratio of PHA substrate and non-PHA substrate in the substrate of the base fabric layer is 2.86:1; the mass ratio of PHA substrate and non-PHA substrate in the substrate of the filling layer and / or foaming layer is 2.85:1; the mass ratio of PHA substrate and non-PHA substrate in the substrate of the simulation layer is 2.88:1.
[0020] In a specific embodiment of the present invention, in the artificial leather, the PHA substrates of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer are PHB, P34HB and PHBHHx, the molar content of 4HB in the P34HB is any value between 3% and 30%, preferably any value between 8% and 24%, for example, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably the molar content of 4HB in the P34HB is 8%, the molar content of 3HHx in the PHBHHx is any value between 1% and 30%, for example, 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably the molar content of 3HHx in the PHBHHx is 20%, preferably, the P In the HA substrate, the added mass of P34HB is any value between 21% and 79%, preferably any value between 25% and 70%, for example, 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%. In a specific embodiment of the present invention, the mass ratio of PHB, P34HB and PHBHHx in the PHA substrate is 9:5:3; the non-PHA substrate in the artificial leather is sugarcane fiber, PPC and PGA, and the mass ratio of sugarcane fiber, PPC and PGA in the non-PHA substrate in the base fabric layer, filling layer, foaming layer and / or simulation layer is 3:4:4; the mass ratio of the PHA substrate and the non-PHA substrate in the substrate in the base fabric layer, filling layer and foaming layer is 3.09:1.
[0021] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHBV, P34HB and PHBHHx, and the molar content of 3HV in the PHBV is any value in the range of 1%-30%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 3HV in the PHBV is 5%, the molar content of 4HB in the P34HB is 3 %-30%, preferably any value in the range of 8%-24%, such as 3%, 5%, 8%, 10%, 15%, 20%, 24%, 25%, 30%, preferably the molar content of 4HB in the P34HB is 10%, the molar content of 3HHx in the PHBHHx is any value in the range of 1%-30%, such as 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably the molar content of 3HHx in the PHBHHx is 10%, The molar content of Hx is 8%. Preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, for example 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%. In a specific embodiment of the present invention, the mass ratio of PHBV, P34HB and PHBHHx in the PHA substrate is 2:1:1; the non-PHA substrate in the artificial leather is soybean protein fiber, bamboo fiber and PBS, and the mass ratio of soybean protein fiber, bamboo fiber and PBS in the non-PHA substrate of the base fabric layer is 3:6:10.5; the mass ratio of soybean protein fiber, bamboo fiber and PBS in the non-PHA substrate of the filling layer, foaming layer and / or simulation layer is 2:4:7; the mass ratio of PHA substrate and non-PHA substrate in the substrate of the base fabric layer, filling layer, foaming layer and / or simulation layer is 2.46:1.
[0022] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHB and P34HB, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%, for example, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 4HB in the P34HB is 16%; preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, for example, 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%. In a specific embodiment of the present invention, the mass ratio of PHB to P34HB in the PHA substrate is 5:4; the non-PHA substrate in the artificial leather is black tea fiber, bamboo fiber and PGA, and the mass ratio of black tea fiber, bamboo fiber and PGA in the non-PHA substrate of the base fabric layer is 9:8:10; the mass ratio of black tea fiber, bamboo fiber and PGA in the non-PHA substrate of the filling layer and / or foaming layer is 6:5.3:6.7; the mass ratio of black tea fiber, bamboo fiber and PGA in the non-PHA substrate of the simulation layer is 3:2.7:3.3; the mass ratio of PHA substrate and non-PHA substrate in the substrates of the base fabric layer, filling layer, foaming layer and simulation layer is 4:1.
[0023] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHB and P34HB, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%, for example, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably, the molar content of 4HB in the P34HB is 16%; preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, for example, 21, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%, in a specific embodiment of the present invention. In the embodiment, the mass ratio of PHB to P34HB in the PHA substrate is 17:8; the non-PHA substrate in the artificial leather is mulberry fiber, bamboo fiber and PBAT, and the mass ratio of mulberry fiber, bamboo fiber and PBAT in the non-PHA substrate of the base fabric layer is 9:5:21; the mass ratio of mulberry fiber, bamboo fiber and PBAT in the non-PHA substrate of the filling layer and / or foaming layer is 6:3.4:14; the mass ratio of mulberry fiber, bamboo fiber and PBAT in the non-PHA substrate of the simulation layer is 3:1.7:7; the mass ratio of PHA substrate and non-PHA substrate in the base fabric layer substrate is 2.86:1; the mass ratio of PHA substrate and non-PHA substrate in the substrates of the filling layer, foaming layer and simulation layer is 2.85:1.
[0024] In a specific embodiment of the present invention, in the artificial leather, the PHA substrate of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer is PHB and P34HB, the molar content of 4HB in the P34HB is any value in the range of 3%-30%, preferably any value in the range of 8%-24%, for example, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, preferably the molar content of 4HB in the P34HB is 16%; preferably, in the PHA substrate, the added mass of P34HB is any value in the range of 21%-79%, preferably any value in the range of 25%-70%, for example, 21 , 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 79%. In a specific embodiment of the present invention, the mass ratio of PHB to P34HB in the PHA substrate is 33:15; the non-PHA substrate in the artificial leather is black tea fiber, soy protein fiber and PBAT, and the mass ratio of black tea fiber, soy protein fiber and PBAT in the non-PHA substrate of the base fabric layer, filling layer, foaming layer and / or simulation layer is 4:4:5; the mass ratio of PHA substrate to non-PHA substrate in the substrate of the base fabric layer, filling layer, foaming layer and simulation layer is 2.46:1. Preferably, the artificial leather also contains auxiliary materials.
[0025] Further preferably, the auxiliary material includes one or both of a filler and / or an ultraviolet absorber.
[0026] In a specific embodiment of the present invention, the artificial leather comprises a PHA substrate, a non-PHA substrate, a filler and an ultraviolet absorber.
[0027] In a specific embodiment of the present invention, the artificial leather comprises a mixed raw material base material of P34HB and non-P34HB PHA, a non-PHA base material, a filler and an ultraviolet absorber.
[0028] More preferably, the filler is a micron-sized filler.
[0029] More preferably, the ultraviolet absorber is a nano-scale inorganic powder.
[0030] Preferably, in the base fabric layer, the mass ratio of the filler to the ultraviolet absorber in the auxiliary material is any value in the range of (3-5):1, such as 3:1, 4:1, or 5:1.
[0031] Preferably, in the filling layer, the mass ratio of the filler and the ultraviolet absorber in the auxiliary material is any value in the range of (5-8):1, for example, 5:1, 6:1, 6.5:1, 7:1, 8:1.
[0032] Preferably, in the simulation layer, the mass ratio of the filler to the ultraviolet absorber in the auxiliary material is any value in the range of (1-3):1, for example, 1:1, 1.5:1, 2:1, 3:1.
[0033] Preferably, in the base fabric layer, the mass ratio of PHA, filler and UV absorber is any value of (35-60):(3-5):1, for example, 35:3:1, 36:4:1, 42:4:1, 45:4:1, 48:4:1, 50:4:1, 54:4:1, 55:4:1, 60:4:1.
[0034] Preferably, in the filling layer, the mass ratio of PHA, filler and UV absorber is any value of (40-80):(5-8):1, for example, 40:5:1, 45:5:1, 48:6.5:1, 50:8:1, 56:6.5:1, 64:6.5:1, 66.6:6.5:1, 66.7:6.5:1, 70:6.5:72:6.5:1, 75:8:1, 80:8:1. Preferably, in the simulation layer, the mass ratio of PHA, filler and UV absorber is any value of (20-40):(1-3):1, for example, 20:1:1, 24:1.5:1, 25:3:1, 28:1.5:1, 30:3:1, 32:1.5:1, 33.3:1.5:1, 33.4:1.5:1, 36:1.5:1, 40:3:1.
[0035] Preferably, in the base fabric layer, the added mass of the filler is 0%-10% of the PHA substrate, preferably 0.1%-10%, and further preferably any value in the range of 5%-8%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0036] Preferably, in the filling layer, the added mass of the filler is 0%-11% of the PHA substrate, preferably 0.1%-11%, and further preferably any value in the range of 5%-11%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5%, 9.6%, 9.7%, 9.8%, 10%, 10.1%, 10.2%, 10.5%, 11%.
[0037] Preferably, fillers are added or not added to the foaming layer. In a specific embodiment of the present invention, fillers are not added to the foaming layer.
[0038] Preferably, in the simulation layer, the added mass of the filler is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.2%, 2.3%, 2.4%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0039] The filler includes but is not limited to one or more of hollow glass microspheres, mica powder or talc powder.
[0040] In a specific embodiment of the present invention, the filler is hollow glass microspheres.
[0041] In a specific embodiment of the present invention, the filler is mica powder.
[0042] In a specific embodiment of the present invention, the filler is talc.
[0043] Preferably, in the base fabric layer, the added mass of the ultraviolet absorber is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2.5%, for example 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.9%, 2%, 2.1%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0044] Preferably, in the filling layer, the added mass of the ultraviolet absorber is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-2.5%, such as 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.5%, 1.6%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. Preferably, in the foaming layer, the added mass of the ultraviolet absorber is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-2%, such as 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.1%, 1.2%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0045] Preferably, in the simulation layer, the added mass of the ultraviolet absorber is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0046] Preferably, the ultraviolet absorber includes but is not limited to one or more of nano ZnO, rutile TiO2 or nano CeO2.
[0047] In a specific embodiment of the present invention, the ultraviolet absorbers in the base fabric layer, the filling layer, the foaming layer and the simulation layer are nano ZnO and rutile TiO2, and the mass ratio of the nano ZnO to rutile TiO2 is 2:3. In a specific embodiment of the present invention, the ultraviolet absorbers in the artificial leather are rutile TiO2 and nano CeO2, and the mass ratio of the rutile TiO2 to nano CeO2 in the base fabric layer, the filling layer and the simulation layer is 1:1; the mass ratio of the rutile TiO2 to nano CeO2 in the foaming layer is 7:8.
[0048] In a specific embodiment of the present invention, the ultraviolet absorbers in the base fabric layer, the filling layer, the foaming layer and the simulation layer are nano ZnO and nano CeO2, and the mass ratio of the nano ZnO to the nano CeO2 is 2:3.
[0049] In a specific embodiment of the present invention, the ultraviolet absorbers in the base fabric layer, the filling layer, the foaming layer and the simulation layer are nano ZnO and rutile TiO2, and the mass ratio of the nano ZnO to rutile TiO2 is 2:3. Preferably, in the base fabric layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (3-7): (1-3): 1; preferably any value in (4-6): (1.5-2): 1, for example 3:1:1, 3:1.5:1, 3:2:1, 3:2.5:1, 3:3:1, 4:1:1, 4:1.5:1, 4:2:1, 4:2.5:1, 4:3:1, 4:4:5:1, 4:5:1, 4:6:1, 4:7:1, 4:8:1, 4:9:1, 4:10:1, 4:11:1, 4:12:1, 4:13:1, 4:14:15:1, 4:15:1, 4:16:1, 4:17:1, 4:18:1, 4:19:1, 4:19:1, 4:20:1, 4:21:1, 4:22:1, 4:23:1, 4:24:1, 4:25:1, 4:26:1, 4:27:1, 4:28:1, 4:29:1, 4:30:1, 4:31:1, 4:32:1, 4:33:1, 4:34:1, 4:35:1, 4:36:1, 4:37:1, 4:38:1, 4:39:1, 4:39:1 1, 8:1.95:1, 5:1:1, 5:1.5:1, 5:1.75:1, 5:2:1, 5:2.5:1, 5:3:1, 5.1:1.65:1, 5.4:1.35:1, 6:1:1, 6:1.5:1, 6:2:1, 6:2.5:1, 6:3:1, 7:1:1, 7:1.5:1, 7:2:1, 7:2.5:1, 7:3:1.
[0050] Preferably, in the filling layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (2-6): (1-3): 1; preferably any value in (3-6): (1-2): 1, for example, 2:1:1, 2:1.5:1, 2:2:1, 2:2.5:1, 2:3:1, 3:1:1, 3:1.5:1, 3:2:1, 3:2.5:1, 3:3:1, 4:1:1, 4:1.5: 1, 4:2:1, 4:2.5:1, 4:3:1, 4.57:1.86:1, 4.76:1.66:1, 4.76:1.67:1, 4.86:1.57:1, 5:1:1, 5:1.5:1, 5:2:1, 5:2.5:1, 5:3:1, 5.14:1.29:1, 6:1:1, 6:1.5:1, 6:2:1, 6:2.5:1, 6:3:1.
[0051] Preferably, in the foaming layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (2-6): (1-3): 1; preferably any value in (3-6): (1-2): 1, for example, 2:1:1, 2:1.5:1, 2:2:1, 2:2.5:1, 2:3:1, 3:1:1, 3:1.5:1, 3:2:1, 3:2.5:1, 3:3:1, 4:1:1, 4:1.5: 1, 4:2:1, 4:2.5:1, 4:3:1, 4.57:1.86:1, 4.76:1.66:1, 4.76:1.67:1, 4.86:1.57:1, 5:1:1, 5:1.5:1, 5:2:1, 5:2.5:1, 5:3:1, 5.14:1.29:1, 6:1:1, 6:1.5:1, 6:2:1, 6:2.5:1, 6:3:1.
[0052] Preferably, in the simulation layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (4-10): (1-3): 1; preferably any value in (5-9): (1.5-2.8): 1, for example, 4:1:1, 4:1.5:1, 4:2:1, 4:2.5:1, 4:3:1, 5:1:1, 5:1.5:1, 5:2:1, 5:2.5:1, 5:3:1, 6:1:1, 6:1.5:1, 6:2:1, 6:2.5:1, 6:3:1 , 6.4:2.6:1, 6.66:2.34:1, 6.68:2.32:1, 6.8:2.2:17:1:1, 7:1.5:1, 7:2:1, 7:2.5:1, 7:3:1, 8:1:1, 8:1.5:1, 8:2:1, 8:2.5:1, 8:3:1, 9:1:1, 9:1.5:1, 9:2:1, 9:2.25:1, 9:2.8:1, 9:3:1, 10:1:1, 10:2:1, 10:3:1.
[0053] Preferably, the auxiliary materials also include, but are not limited to, one, two or more of a chain extender, an environmentally friendly plasticizer, an anti-hydrolysis agent, an antioxidant, a heat stabilizer or a foaming agent.
[0054] Preferably, in the base fabric layer, the added mass of the chain extender is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-3%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.9%, 2%, 2.1%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0055] Preferably, in the filling layer, the added mass of the chain extender is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-3.5%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.2%, 2.3%, 2.4%, 3%, 3.1%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0056] Preferably, in the foaming layer, the added mass of the chain extender is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-4.5%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.9%, 3%, 3.1%, 4%, 4.1%, 4.2%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%.
[0057] Preferably, in the simulation layer, the added mass of the chain extender is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-3.5%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.2%, 2.3%, 2.4%, 2.5%, 2.9%, 3%, 3.1%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0058] The chain extender includes, but is not limited to, one or more of sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, dimethylolpropionic acid, dimethyldiallylammonium chloride, 1,4-butanediol, BASF ADR 4400 or BASF ADR 4468.
[0059] In a specific embodiment of the present invention, the chain extenders in the base fabric layer, filling layer, foaming layer and / or simulation layer of the artificial leather are sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, dihydroxymethylpropionic acid (DMPA) and BASFADR 4400, and the mass ratio of sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, dihydroxymethylpropionic acid (DMPA) and BASF ADR4400 is 3:3:4.
[0060] In a specific embodiment of the present invention, the chain extender in the base fabric layer, filling layer, foaming layer and / or simulation layer of the artificial leather is sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, 1,4-butanediol and BASF ADR4468, and the mass ratio of sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, 1,4-butanediol and BASF ADR 4468 is 3:2:5.
[0061] In a specific embodiment of the present invention, the chain extender in the base fabric layer, filling layer, foaming layer and / or simulation layer of the artificial leather is dimethyldiallyl ammonium chloride (DMDAAC), dihydroxymethylpropionic acid (DMPA) and BASF ADR4400, and the mass ratio of dimethyldiallyl ammonium chloride (DMDAAC), dihydroxymethylpropionic acid (DMPA) and BASF ADR 4400 is 2:3:5.
[0062] In a specific embodiment of the present invention, the chain extender in the base fabric layer, filling layer, foaming layer and / or simulation layer of the artificial leather is dimethyldiallyl ammonium chloride (DMDAAC), 1,4-butanediol and BASF ADR 4468, and the mass ratio of dimethyldiallyl ammonium chloride (DMDAAC), 1,4-butanediol and BASF ADR 4468 is 2:1:2.
[0063] Preferably, in the base fabric layer, the added mass of the environmentally friendly plasticizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2.5%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.9%, 2%, 2.1%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0064] Preferably, in the filling layer, the added mass of the environmentally friendly plasticizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2.5%, for example 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.9%, 2%, 2.2%, 2.3%, 2.4%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0065] Preferably, in the foaming layer, the added mass of the environmentally friendly plasticizer is 0%-10% of the PHA substrate, preferably 0.1%-10%, and further preferably any value in the range of 1%-8%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 6.6%, 6.7%, 6.8%, 7%, 7.1%, 8%, 9%, 10%.
[0066] Preferably, in the simulation layer, the added mass of the environmentally friendly plasticizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-3.5%, for example 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.9%, 3%, 3.1%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0067] The environmentally friendly plasticizer includes but is not limited to one or both of acetyl tributyl citrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.
[0068] In a specific embodiment of the present invention, the environmentally friendly plasticizer is acetyl tributyl citrate.
[0069] In a specific embodiment of the present invention, the environmentally friendly plasticizer is 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.
[0070] Preferably, in the base fabric layer, the added mass of the anti-hydrolysis agent is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.5%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0071] Preferably, in the filling layer, the added mass of the anti-hydrolysis agent is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0072] Preferably, in the foaming layer, the added mass of the anti-hydrolysis agent is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0073] Preferably, in the simulation layer, the added mass of the anti-hydrolysis agent is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0074] Preferably, the anti-hydrolysis agent includes, but is not limited to, one or more of anti-hydrolysis agent HYY-003, bis(2,6-diisopropylbenzene)carbodiimide or anti-hydrolysis agent HD900A.
[0075] In a specific embodiment of the present invention, the anti-hydrolysis agent in the base fabric layer, the filling layer, the foaming layer and the simulation layer is the anti-hydrolysis agent HYY-003.
[0076] In a specific embodiment of the present invention, the anti-hydrolysis agent in the artificial leather is anti-hydrolysis agent HYY-003 and anti-hydrolysis agent HD900A, and the mass ratio of anti-hydrolysis agent HYY-003 and anti-hydrolysis agent HD900A in the base fabric layer is 1:2; the anti-hydrolysis agent in the filling layer, the foaming layer and the simulation layer is anti-hydrolysis agent HYY-003 and anti-hydrolysis agent HD900A, and the mass ratio of anti-hydrolysis agent HYY-003 and anti-hydrolysis agent HD900A is 3:7.
[0077] In a specific embodiment of the present invention, the anti-hydrolysis agent in the artificial leather is anti-hydrolysis agent HYY-003 and bis(2,6-diisopropylbenzene)carbodiimide, and the mass ratio of the anti-hydrolysis agent HYY-003 and bis(2,6-diisopropylbenzene)carbodiimide in the base fabric layer is 1:2. The anti-hydrolysis agent in the filling layer, foaming layer and simulation layer is anti-hydrolysis agent HYY-003 and bis(2,6-diisopropylbenzene)carbodiimide, and the mass ratio of the anti-hydrolysis agent HYY-003 and bis(2,6-diisopropylbenzene)carbodiimide is 3:7.
[0078] In a specific embodiment of the present invention, the anti-hydrolysis agents in the base fabric layer, the filling layer, the foaming layer and the simulation layer are bis(2,6-diisopropylbenzene)carbodiimide and anti-hydrolysis agent HD900A, and the mass ratio of bis(2,6-diisopropylbenzene)carbodiimide and anti-hydrolysis agent HD900A is 3:2.
[0079] Preferably, in the base fabric layer, the added mass of the antioxidant is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2.5%, for example 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.9%, 2%, 2.1%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0080] Preferably, in the filling layer, the added mass of the antioxidant is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.8%, 1.9%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0081] Preferably, in the foaming layer, the added mass of the antioxidant is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0082] Preferably, in the simulation layer, the added mass of the antioxidant is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value between 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.4%, 1.47%, 1.48%, 1.49%, 1.5%, 1.56%, 1.6%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0083] Preferably, the antioxidant includes, but is not limited to, one or more of antioxidant 2777, tris(2,4-di-tert-butylphenyl) phosphite or antioxidant S-9228.
[0084] In a specific embodiment of the present invention, the antioxidant is antioxidant 2777.
[0085] In a specific embodiment of the present invention, the antioxidant is tris(2,4-di-tert-butylphenyl) phosphite.
[0086] In a specific embodiment of the present invention, the antioxidant is antioxidant S-9228.
[0087] Preferably, in the base fabric layer, the added mass of the heat stabilizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-3%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.4%, 2.5%, 2.6%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0088] Preferably, in the filling layer, the added mass of the heat stabilizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.8%, 1.83%, 1.87%, 1.9%, 1.95%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0089] Preferably, in the foaming layer, the added mass of the heat stabilizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and more preferably any value in the range of 1%-2%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.8%, 1.83%, 1.87%, 1.9%, 1.95%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0090] Preferably, in the simulation layer, the added mass of the heat stabilizer is 0%-10% of the PHA substrate, preferably 0.1%-5%, and further preferably any value in the range of 1%-2.5%, for example, 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 2%, 2.2%, 2.3%, 2.4%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.
[0091] Preferably, the thermal stabilizer includes but is not limited to one or more of stearate, nanocellulose or fumed nanosilica.
[0092] In a specific embodiment of the present invention, the heat stabilizers in the artificial leather are zinc stearate and gas-phase nano-silicon dioxide, the mass ratio of zinc stearate and gas-phase nano-silicon dioxide in the base fabric layer, the filling layer and the foaming layer is 2:3; the mass ratio of zinc stearate and gas-phase nano-silicon dioxide in the simulation layer is 1:2.
[0093] In a specific embodiment of the present invention, the heat stabilizers in the artificial leather are nanocellulose and gas-phase nanosilica, the mass ratio of nanocellulose and gas-phase nanosilica in the base fabric layer, the filling layer and the foaming layer is 9:16; the mass ratio of nanocellulose and gas-phase nanosilica in the simulation layer is 1:2.
[0094] In a specific embodiment of the present invention, the heat stabilizers in the base fabric layer, the filling layer, the foaming layer and the simulation layer are calcium stearate and nanocellulose, and the mass ratio of the calcium stearate to the nanocellulose is 3:2.
[0095] In a specific embodiment of the present invention, the heat stabilizers in the artificial leather are zinc stearate and gas-phase nano-silicon dioxide, the mass ratio of zinc stearate and gas-phase nano-silicon dioxide in the base fabric layer, the filling layer and the foaming layer is 2:3; the mass ratio of zinc stearate and gas-phase nano-silicon dioxide in the simulation layer is 1:2.
[0096] Preferably, the foaming layer of the artificial leather further comprises a foaming agent.
[0097] Preferably, in the foaming layer, the added mass of the foaming agent is 0%-10% of the PHA substrate, preferably 0.1%-10%, and more preferably any value in the range of 1%-6%, such as 0.00001%, 0.1%, 0.2%, 0.5%, 1%, 1.8%, 1.9%, 2%, 3%, 4%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 6%, 7%, 8%, 9%, 10%. Preferably, the foaming agent includes but is not limited to one or more of azodicarbonamide, foaming agent SP1000C, leather foaming agent HF-800, sodium bicarbonate or ammonium bicarbonate.
[0098] In a specific embodiment of the present invention, the foaming agent is azodicarbonamide, leather foaming agent HF-800 and sodium bicarbonate, and the mass ratio of azodicarbonamide, leather foaming agent HF-800 and sodium bicarbonate is 15:8:12.
[0099] In a specific embodiment of the present invention, the foaming agent is azodicarbonamide, foaming agent SP1000C and ammonium bicarbonate, and the mass ratio of azodicarbonamide, foaming agent SP1000C and ammonium bicarbonate is 15:12:8. Preferably, the artificial leather can be prepared by any preparation method in the prior art.
[0100] The second aspect of the present invention provides a method for preparing artificial leather.
[0101] Preferably, the artificial leather comprises a base fabric layer, a filling layer, a foaming layer and / or a simulation layer, and the raw materials of the base fabric layer, the filling layer, the foaming layer and / or the simulation layer comprise a substrate, and the substrate comprises a PHA substrate.
[0102] Preferably, the substrate also includes a non-PHA substrate.
[0103] More preferably, the artificial leather further comprises auxiliary materials.
[0104] Preferably, the types and addition amounts of the PHA substrate, non-PHA substrate and auxiliary materials are the same as those defined in the first aspect. Preferably, the preparation method comprises preparing a base fabric layer, a filling layer, a foaming layer and / or a simulation layer.
[0105] The method for preparing the base fabric layer comprises:
[0106] A1: Mix the base material and auxiliary materials, melt them, cool them and granulate them to obtain fiber-specific granules;
[0107] A2: The fiber-specific pellets are melt-extruded and filaments or non-woven fabrics are obtained through a molding process to obtain a base fabric layer. Preferably, the molding process includes a fiber web reinforcement molding process, and the fiber web reinforcement molding process includes different spinnerets, spinning processes, and subsequent drafting and winding or hydroentanglement, needle punching, etc.
[0108] Preferably, the step A2 further comprises unwinding the filaments and obtaining the base fabric through a knitting or weaving process.
[0109] The preparation of the filling layer comprises:
[0110] B1: Mix the base material and auxiliary materials, melt them, cool them and granulate them to obtain granules specially used for the filling layer;
[0111] B2: The pellets specially used for the filling layer are melted and then cast into a film to obtain the filling layer.
[0112] The preparation of the foaming layer comprises:
[0113] C1: The base material and the auxiliary material are mixed, plasticized and then calendered into a film to obtain a foaming layer.
[0114] The preparation of the simulation layer comprises:
[0115] D1: Mix the base material and auxiliary materials, melt them, cool them and granulate them to obtain granules specially used for the simulation layer;
[0116] D2: The special pellets for the simulation layer are melted and cast into a film to obtain the simulation layer.
[0117] Preferably, the melting described in A1, A2, B1, B2 and / or D1 includes using a twin-screw extruder, and the reaction temperature is 120-230°C, preferably any value in the range of 150-215°C, for example 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C.
[0118] Preferably, the cooling described in A1, B1 and / or D1 includes using water cooling or air cooling.
[0119] Further preferably, the air cooling includes side blowing or ring blowing.
[0120] More preferably, the air cooling is ring blowing, and the air supply temperature is 15-70°C, preferably any value in the range of 18-65°C, for example 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70°C.
[0121] Preferably, the weight of the base fabric in A2 is 20-450 g / m 2 ; preferably 30-400g / m 2any value, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 350, 400, 450 g / m 2 Preferably, the nonwoven fabric A2 has a gram weight of 20-450 g / m 2 ; preferably 30-400g / m 2 any value, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 350, 400, 450 g / m 2 Preferably, the casting temperature of B2 and D2 is 120-230°C, preferably any value in the range of 150-215°C, for example, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C.
[0122] Preferably, the thickness of the cast film obtained by the cast film forming process B2 is 60-800 μm, preferably any value in the range of 70-700 μm, for example, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 500, 600, 700, 800 μm.
[0123] Preferably, the thickness of the cast film obtained by the cast film forming in D2 is 30-500 μm, preferably any value in the range of 35-420 μm, for example, 30, 35, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 175, 180, 190, 200, 300, 400, 420, 500 μm.
[0124] Preferably, the plasticizing described in C1 includes using a twin-screw extruder, and the plasticizing temperature is 100-200° C., preferably any value in the range of 120-195° C., such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 195, 200° C. Preferably, the foaming temperature described in C1 is 40-150° C., preferably any value in the range of 40-105° C., such as 40, 50, 60, 70, 80, 90, 100, 105, 110, 120, 130, 140, 150° C.
[0125] The foaming time is 10-50 min, preferably any value between 15-30 min, for example, 10, 15, 20, 25, 30, 35, 40, 45, 50 min.
[0126] Preferably, the thickness of the foamed layer obtained by C1 is 200-3500 μm, preferably any value in the range of 280-3000 μm, for example, 200, 280, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 2000, 2500, 3000, 3500 μm.
[0127] Preferably, the preparation method further comprises compounding the base fabric layer, the filling layer, the foaming layer and / or the simulation layer.
[0128] Preferably, the compounding includes heating, and the heating temperature is 50-150°C, preferably any value in the range of 60-110°C, for example 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150°C.
[0129] In a specific embodiment of the present invention, the preparation method comprises:
[0130] Preparation of base fabric layer:
[0131] A1: In parts by mass, 45-90 parts (preferably any value in the range of 50-80 parts, such as 45, 50, 55, 60, 65, 67.5, 70, 75, 80, 85, 90 parts) of the base material and 0-20 parts (preferably any value in the range of 8-12 parts, such as 0, 5, 10, 15, 20 parts) of the auxiliary material are weighed and mixed, and melted and cooled to form granules through a twin-screw extruder, wherein the barrel temperature is set to 120-230°C (preferably 150-215°C, for example, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C), using ring blowing, the air supply temperature is 15-70°C (preferably any value in 18-65°C, for example, 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70°C), to obtain fiber-specific pellets;
[0132] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 20-450g / m 2 (Preferably 30-400g / m 2 any value, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 350, 400, 450 g / m 2 );
[0133] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a filament with a gram weight of 20-450 g / m 2 (Preferably 30-400g / m 2 any value, for example, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 350, 400, 450 g / m 2 )'s PHA base fabric, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0134] Prepare the filling layer and compound the filling layer and the base fabric layer:
[0135] B1: In parts by mass, 60-120 parts (preferably any value in the range of 80-100 parts, such as 60, 70, 80, 90, 100, 110, 120 parts) of the base material and 0-28 parts (preferably any value in the range of 12-16 parts, such as 0, 5, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28 parts) of the auxiliary material are weighed and mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature is set to 120-23 0°C (preferably any value in the range of 150-215°C, such as 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C), using annular blowing, the air supply temperature is 15-70°C (preferably any value in the range of 18-65°C, such as 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70°C), to obtain a special granular material for the filling layer;
[0136] B2: The pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and cast into a film to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 50-150°C (preferably any value in the range of 60-110°C, such as 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150°C), and the casting temperature is 120-230°C (preferably any value in the range of 150-215°C, such as 120, 130, 140, 150, 160, , 170, 180, 190, 200, 210, 220, 230°C), and the cast film thickness is 60-800 μm (preferably any value in 70-700 μm, for example 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 500, 600, 700, 800 μm).
[0137] Prepare the foaming layer and compound the foaming layer with the base fabric layer / filling layer:
[0138] C1: 60-120 parts (preferably any value in the range of 80-100 parts, such as 60, 70, 80, 90, 100, 110, 120 parts) of the base material and 0-28 parts (preferably any value in the range of 12-16 parts, such as 0, 5, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28 parts) of the auxiliary material are weighed, mixed and dried, injected into a twin-screw extruder with a heating device for plastication, and formed into a film by calendering, i.e., a foaming layer, and then subjected to three-dimensional mixing. The roller setting machine makes it tightly compounded with the pre-heated PHA base fabric / filling layer, and the foaming layer is close to the filling layer. Since the two layers are mainly made of the same material, no adhesive is required, and then it is sent to the foaming furnace for foaming, wherein the plasticizing temperature is 100-200°C (preferably any value in the range of 120-195°C, such as 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 195, 200°C), and the pre-heating temperature is 50-150°C The foaming temperature is 40-150°C (preferably any value in the range of 40-105°C, for example 40, 50, 60, 70, 80, 90, 100, 105, 110, 120, 130, 140, 150°C), and the foaming time is 10-50 min (preferably 15-30 min, for example The foam layer is expanded and cooled for a final thickness of 200-3500 μm (preferably any value between 280 and 3000 μm, for example 200, 280, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 2000, 2500, 3000, 3500 μm).
[0139] Prepare the simulation layer and compound the simulation layer with the base fabric layer / filling layer / foaming layer:
[0140] D1: In parts by mass, 30-60 parts (preferably any value in 40-50 parts, such as 30, 35, 40, 45, 50, 55, 60 parts) of the base material and 0-12 parts (preferably any value in 4-8 parts, such as 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 parts) of the auxiliary material are weighed and mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 120-230°C (preferably Any value in the range of 150-215°C, such as 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C), using ring blowing, the air supply temperature is 15-70°C (preferably any value in the range of 18-65°C, such as 15, 18, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70°C), to obtain special granules for the simulation layer;
[0141] D2: The pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base fabric / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 50-150°C (preferably any value in the range of 60-110°C, such as 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150°C), and the casting temperature is 120-230°C The temperature of the cast film is preferably any value in the range of 150-215°C, for example 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 215, 220, 230°C), and the thickness of the cast film is 30-500μm (preferably any value in the range of 35-420μm, for example 30, 35, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 175, 180, 190, 200, 300, 400, 420, 500μm). The third aspect of the present invention provides an artificial leather obtained by the above preparation method.
[0142] A fourth aspect of the present invention provides an application of the artificial leather and / or the artificial leather prepared by the above preparation method.
[0143] Preferably, the application includes application in the manufacture of leather products, simulated skin or antibacterial wound dressings; further preferably, the leather products include automobile interiors, leather furniture, leather shoes, and leather clothing.
[0144] The term "include" or "comprising" in the present invention is an open description containing the specified components or steps described, and other specified components or steps that will not be substantially affected.
[0145] The term "and / or" of the present invention includes all combinations of items connected by the term, and each combination should be deemed to have been listed separately herein. For example, "A and / or B" includes "A", "A and B" and "B". For another example, "A, B and / or C" includes "A", "B", "C", "A and B", "A and C", "B and C" and "A and B and C".
[0146] Beneficial effects of the present invention:
[0147] 1. The artificial leather of the present invention is mainly made of environmentally friendly and degradable PHA. No solvents or adhesives are required in the entire process from raw materials to production, use, recycling or disposal. It can be fully degraded in the natural environment, truly achieving environmental friendliness throughout the entire life cycle. It not only avoids the slaughter of animals and the damage to the ecological environment caused by traditional leather, but also has the advantages of environmental protection, degradation and high recycling rate that ordinary artificial leather does not have.
[0148] 2. The artificial leather of the present invention is soft to the touch, good in elasticity, good in skin affinity, antibacterial, mildew-proof, waterproof, breathable, and easy to dye by adjusting the type and proportion of the substrate, and based on the excellent biophilic, hydrophobic, antibacterial, and easy-to-dye properties of PHA itself. In particular, the reasonable compounding of P34HB and other types of PHA ensures that the PHA artificial leather has both soft hand feel and strong mechanical properties. PHA is dominant relative to other degradable substrates, and the overall degradation rate and dyeing performance are also improved. There is no need to add fluorine-containing or silicon-containing hydrophobic treatment agents during the preparation process. Only by relying on the natural hydrophobicity of PHA as an ester substance, the ideal waterproof effect can be achieved.
[0149] 3. The artificial leather of the present invention unexpectedly found through experiments that the content of 4HB in P34HB and the amount of P34HB added have a great influence on the foaming effect, that is, within a certain range, a lower foam density and a higher expansion coefficient can be obtained by reducing the content of 4HB or the amount of P34HB added. However, considering that the softness of artificial leather can be improved by increasing the content of 4HB or the amount of P34HB added, there is a narrower applicable range for the content of 4HB in P34HB and the amount of P34HB added. Experiments have shown that too high or too low an amount of 4HB or P34HB added will affect the overall performance of artificial leather. In addition, the increase of the expansion coefficient within a certain range can improve the sound insulation effect.
[0150] 4. The artificial leather of the present invention, the obtained PHA artificial leather is divided into four layers, namely, a base fabric layer, a filling layer, a foaming layer and a simulation layer. Among them, the base fabric layer can be made of non-woven fabrics or knitted or woven fabrics of different weights, with filling layers and foaming layers of different thicknesses, so that it can be adapted to various leather application fields such as automotive interiors, furniture, leather shoes and leather clothes, and decorations. Since the main materials of the four layers are all PHA, the layers are tightly combined with each other, the peeling strength is high, and the use of adhesives is avoided, further improving the environmental protection characteristics.
[0151] 5. The artificial leather of the present invention adopts a special foaming process. The traditional foaming process generally requires the addition of solvents or even volatile solvents to obtain resins, and the foaming furnace generally performs most of the foaming process rather than micro-foaming. The method described in the present invention does not add solvents or use resins containing volatile solvents. Due to the addition of chain extenders, anti-hydrolysis agents, antioxidants, thermal stabilizers, etc., the melt strength is greatly improved, so that the material through plasticization has the characteristics of unopened macroporous foaming, and the foam will not break due to low melt strength. Combined with the microporous foaming caused by the subsequent foaming furnace, the overall foam density of the foaming layer is low, the expansion coefficient is high, and the foam holes are fine, which ensures the soft feel, resilience and air permeability of the finished artificial leather.
[0152] 6. The artificial leather of the present invention has an appropriate mass ratio of "base fabric layer (fiber material)" to "filling layer + foaming layer + simulation layer (elastic material)" between (1:5) and (2:5). If the ratio of the base fabric layer is too low, the artificial leather will have a quality style similar to rubber; if the ratio of the base fabric layer is too high, the artificial leather will have a quality style similar to paper, and both cannot achieve the ideal simulation effect that can replace natural leather.
[0153] 7. The raw materials used in each layer of the artificial leather of the present invention are roughly the same type, but the emphasis is on different proportions. For example, an appropriate amount of natural plant fiber is added to the base fabric layer, more fillers are added to the filling layer, and more flexible substances (such as foaming agents and / or environmentally friendly plasticizers, etc.) are added to the foaming layer. Only in this way can the layers fit tightly and firmly, and at the same time have their own characteristics, forming a differentiated structure, and ultimately making the PHA artificial leather finished product have many excellent properties and functions.
[0154] 8. The artificial leather of the present invention, since the raw materials used in each layer are mainly PHA, was unexpectedly found to have self-repairing properties (high folding fastness) during use, that is, slight scratches on the surface can be removed by applying grease, wiping, and loosening and storing. This may be related to its own degradation performance and lipophilic and biophilic properties, making it longer in use and more cost-effective.
[0155] 9. In the artificial leather of the present invention, the anti-ultraviolet agent is compounded with nano-scale inorganic powder, which is more environmentally friendly than organic ultraviolet absorbers. In addition, the addition of fillers and ultraviolet absorbers unexpectedly has a sound insulation effect, which further expands its application. After analysis, this may be because the micron-scale fillers and nano-scale ultraviolet absorbers are evenly dispersed and interact with the base fabric layer and the filling layer, filling the gaps therein to form a dense sound insulation structure; and the nano-scale ultraviolet absorbers combined with the loose structure of the foaming layer make the sound constantly reflected in the two outermost layers, causing the loss of sound energy, thereby achieving a sound insulation effect.
[0156] The abbreviations and full names of the present invention are shown in Table 1:
[0157] Table 1
[0158]
[0159] BRIEF DESCRIPTION OF THE DRAWINGS
[0160] Figure 1 : Schematic diagram of artificial leather, wherein 1 is the base fabric layer, 2 is the filling layer, 3 is the foaming layer, and 4 is the simulation layer. DETAILED DESCRIPTION
[0161] Performance testing method:
[0162] (1) Softness: A subjective evaluation method was used and two groups of people were selected as subjects.
[0163] A group of 10 experts or experienced subjects, with a weight of 1. They are familiar with the scales and descriptive terms used in subjective tests, and know the human feelings corresponding to each level in the terminology. They can quickly and accurately evaluate and quantify the performance of artificial leather;
[0164] The other group consisted of 10 consumers who had undergone simple training, with a weight of 0.5. Before the experiment, these subjects needed to be given knowledge about the performance of artificial leather and explanations of the terminology of the evaluation scale, so that they could make a correct evaluation of the performance of artificial leather and ensure the rigor of the results.
[0165] Experimental conditions: temperature 20℃±2℃, relative humidity 65%±2%, wind speed ≤0.1m / s.
[0166] The softness performance evaluation scale and description vocabulary are shown in Table 2.
[0167] Table 2: Subjective evaluation scale for softness
[0168] grade 1 2 3 4 5 describe Harder hands General softness soft Very soft Very soft and delicate
[0169] (2) Foam density: the density of the foaming layer after foaming, which can be calculated by the ratio of the mass to volume of the foaming layer after foaming.
[0170] (3) Expansion coefficient: It can be calculated by the ratio of the density of the foaming layer before foaming to the density after foaming.
[0171] Some of the materials used in this invention come from:
[0172] Hollow glass microspheres: purchased from: Zhongke Huaxing New Materials Co., Ltd., item number: C30;
[0173] Mica powder: purchased from Shijiazhuang Huabang Mineral Products Co., Ltd., item number: white, 1250 mesh;
[0174] Talc: purchased from Langfang Yinma Pigment Co., Ltd., item number: YM-T160;
[0175] Nano ZnO: purchased from Beijing Dekedaojin Technology Co., Ltd., product number: DK-ZnO-30;
[0176] Rutile TiO2: purchased from Langfang Yinma Pigment Co., Ltd., product number: YMR-505;
[0177] Nano-CeO2: purchased from Beijing Dekedaojin Technology Co., Ltd., product number: DK-CeO2-20;
[0178] Sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., purity: 99%;
[0179] Dimethylolpropionic acid (DMPA): purchased from: Mitsui Chemicals (Shandong) Co., Ltd., purity: superior grade, 99%; Dimethyldiallylammonium chloride (DMDAAC): purchased from: Hubei Shuangyan Chemical Co., Ltd., item number: GY172; 2,2,4-trimethyl-1,3-pentanediol diisobutyrate: purchased from: Zhongshan Dixin Chemical Co., Ltd., item number: viscosity reducer TXIB;
[0180] Anti-hydrolysis agent HYY-003: purchased from: Shenzhen Heyanyue Plastic Pigment Additive Co., Ltd.;
[0181] Anti-hydrolysis agent HD900A: purchased from Ningbo Hengze Chemical Co., Ltd.
[0182] Bis(2,6-diisopropylbenzene)carbodiimide: purchased from Wuhan Chengtian Fine Chemical Co., Ltd.
[0183] Antioxidant 2777: purchased from: Cytec Corporation, USA, product number: Cytec 2777;
[0184] Tris(2,4-di-tert-butylphenyl) phosphite: purchased from Guangzhou Ruishi Biotechnology Co., Ltd.;
[0185] Antioxidant S-9228: purchased from Dover Chemical, USA;
[0186] Nanocellulose: purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., product number: CNF, 20-50 nm;
[0187] Fumed nano-silica: purchased from Hubei Huifu Nanomaterials Co., Ltd., product number: HL-200;
[0188] Foaming agent SP1000C: purchased from: Zhejiang Shuntai Rubber & Plastic Technology Co., Ltd.;
[0189] Leather foaming agent HF-800: purchased from: Yancheng Zhongmai Rubber and Plastic Products Co., Ltd.;
[0190] The various PHAs used in the present invention are sourced from Beijing Microstructure Biotechnology Co., Ltd.
[0191] Example 1: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather
[0192] A1: 30 parts of PHB, 20 parts of P34HB (4HB content is 16 mol%), 4.5 parts of black tea fiber, 3 parts of mulberry fiber, 10 parts of PBS and 4 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 0.75 parts of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silicon dioxide were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205°C, annular blowing was adopted, and the air supply temperature was 18-65°C to obtain fiber-specific granules;
[0193] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0194] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0195] B1: by weight, 40 parts of PHB, 26.7 parts of P34HB (4HB content is 16 mol%), 6 parts of black tea fiber, 4 parts of mulberry fiber, 13.3 parts of PBS and 6.5 parts of mica powder, 0.45 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.45 parts of dihydroxymethyl propionic acid (DMPA), 0.6 parts of BASF ADR 4400, 1.5 parts of acetyl citrate tributyl ester, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1.25 parts of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205 ° C, annular blowing was adopted, and the air supply temperature was 18-65 ° C to obtain a special granular material for the filling layer;
[0196] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0197] C1: By mass, 40 parts of PHB, 26.7 parts of P34HB (4HB content is 16 mol%), 6 parts of black tea fiber, 4 parts of mulberry fiber, 13.3 parts of PBS and 0.6 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.6 parts of dihydroxymethyl propionic acid (DMPA), 0.8 parts of BASF ADR 4400, 4.5 parts of acetyl citrate tributyl ester, 0.3 parts of nano ZnO, 0.45 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica, 1.5 parts of azodicarbonamide, 0.8 parts of leather foaming agent HF-800, 1.2 parts of sodium bicarbonate were mixed and dried, injected into a twin-screw extruder with a heating device for plastication, and formed into a film by calendaring. The foaming layer is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are made of the same main material, no adhesive is required. Then it is sent to a foaming furnace for foaming, wherein the plasticizing temperature is 120-195°C, the pre-heating temperature is 65-105°C, the foaming temperature is 45-100°C, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0198] D1: by weight, 20 parts of PHB, 13.3 parts of P34HB (4HB content is 16 mol%), 3 parts of black tea fiber, 2 parts of mulberry fiber, 6.7 parts of PBS and 0.75 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.2 parts of nano ZnO, 0.3 parts of rutile TiO2, 0.5 parts of anti-hydrolysis agent HYY-003, 0.5 parts of antioxidant 2777, 0.25 parts of zinc stearate, 0.5 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205 ° C, annular blowing was used, and the air supply temperature was 18-65 ° C to obtain granules for the simulation layer;
[0199] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0200] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0201] The test results of the properties of the obtained artificial leather are shown in Table 3 below. Figure 1 .
[0202] Table 3 Test data of PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather
[0203]
[0204]
[0205] Example 2: PHBV / P34HB+soy protein fiber+PLA+PBAT composite artificial leather
[0206] A1: By mass, weigh 25 parts of PHBV (3HV content is 5 mol%), 25 parts of P34HB (4HB content is 12 mol%), 4.5 parts of soy protein fiber, 5 parts of PLA, 8 parts of PBAT and 4 parts of talc, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.2 parts of 1,4-butanediol, 0.5 parts of BASF ADR 4468, 1 part of acetyl tributyl citrate, 0.5 part of rutile TiO2, 0.5 part of nano CeO2, 0.25 part of anti-hydrolysis agent HYY-003, 0.5 part of anti-hydrolysis agent HD900A, 1 part of tris(2,4-di-tert-butylphenyl) phosphite, 0.45 part of nano cellulose, 0.8 part of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is used, and the air supply temperature is 18-65°C to obtain fiber-specific granules;
[0207] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0208] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0209] B1: By mass, weigh 33.3 parts of PHBV (3HV content is 5 mol%), 33.3 parts of P34HB (4HB content is 12 mol%), 6 parts of soy protein fiber, 6.7 parts of PLA, 10.7 parts of PBAT and 6.5 parts of talc, 0.45 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of 1,4-butanediol, 0.75 parts of BASF ADR 4468, 1.5 parts of acetyl tributyl citrate, 0.5 parts of rutile TiO2, 0.5 parts of nano CeO2, 0.3 parts of anti-hydrolysis agent HYY-003, 0.7 parts of anti-hydrolysis agent HD900A, 1.25 parts of tris(2,4-di-tert-butylphenyl) phosphite, 0.45 parts of nano cellulose, and 0.8 parts of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is used, and the air supply temperature is 18-65°C to obtain granules special for the filling layer;
[0210] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0211] C1: By mass, weigh 33.3 parts of PHBV (3HV content is 5 mol%), 33.3 parts of P34HB (4HB content is 12 mol%), 6 parts of soy protein fiber, 6.7 parts of PLA, 10.7 parts of PBAT and 0.6 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.4 parts of 1,4-butanediol, 1 part of BASF ADR 4468, 4.5 parts of acetylcitrate tributyl ester, 0.35 parts of rutile TiO2, 0.4 parts of nano CeO2, 0.3 parts of anti-hydrolysis agent HYY-003, 0.7 parts of anti-hydrolysis agent HD900A, 1 part of tris (2,4-di-tert-butylphenyl) phosphite, 0.45 parts of nano cellulose, 0.8 parts of fumed nano silicon dioxide, 1.5 parts of azodicarbonamide, 1.2 parts of foaming agent SP1000C, 0.8 parts of ammonium bicarbonate were mixed and dried, and injected into a twin-screw extruder with a heating device. After plastication out of the machine, it is formed into a film by calendering, which is the foaming layer. It is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are mainly made of the same material, no adhesive is required. Then it is sent to the foaming furnace for foaming. The plastication temperature is 120-195℃, the preheating temperature is 65-105℃, the foaming temperature is 45-100℃, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0212] D1: By mass, weigh 16.7 parts of PHBV (3HV content is 5 mol%), 16.7 parts of P34HB (4HB content is 12 mol%), 3 parts of soy protein fiber, 3.3 parts of PLA, 5.3 parts of PBAT, 0.75 parts of talc, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.2 parts of 1,4-butanediol, 0.5 parts of BASF ADR 4468, 1 part of acetyl tributyl citrate, 0.25 part of rutile TiO2, 0.25 part of nano CeO2, 0.15 part of anti-hydrolysis agent HYY-003, 0.35 part of anti-hydrolysis agent HD900A, 0.5 part of tris(2,4-di-tert-butylphenyl) phosphite, 0.25 part of nano cellulose, 0.5 part of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is used, and the air supply temperature is 18-65°C to obtain granules special for the simulation layer;
[0213] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0214] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0215] The test results of the properties of the obtained artificial leather are shown in Table 4 below. Figure 1 .
[0216] Table 4 Test data of PHBV / P34HB+soy protein fiber+PLA+PBAT composite artificial leather
[0217]
[0218]
[0219] Example 3: PHB / P34HB / PHBHHx+sugarcane fiber+PPC+PGA composite artificial leather
[0220] A1: By mass, weigh 27 parts of PHB, 15 parts of P34HB (4HB content is 8 mol%), 9 parts of PHBHHx (3HHx content is 20 mol%), 4.5 parts of sugarcane fiber, 6 parts of PPC, 6 parts of PGA and 4 parts of hollow glass microspheres, 0.2 parts of dimethyldiallyl ammonium chloride (DMDAAC), 0.3 parts of dihydroxymethylpropionic acid (DMPA), 0.5 parts of BASF ADR 4400, 1 part of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.4 part of nano ZnO, 0.6 part of nano CeO2, 0.25 part of anti-hydrolysis agent HYY-003, 0.5 part of bis (2,6-diisopropylbenzene) carbodiimide, 1 part of antioxidant S-9228, 0.75 part of calcium stearate, 0.5 part of nano cellulose were mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature was set A2: vacuum drying the fiber-specific pellets, injecting them into an extrusion device with a heating device to melt them, extruding them through a screw, and combining different spinneret components, spinning processes, and subsequent drawing and winding or spunlace, needle punching and other fiber web reinforcement molding processes to obtain PHA filaments or PHA non-woven fabrics. The weight of the PHA non-woven fabric is 30-400g / m 2 between;
[0221] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0222] B1: By mass, weigh 36 parts of PHB, 20 parts of P34HB (4HB content is 8 mol%), 12 parts of PHBHHx (3HHx content is 20 mol%), 6 parts of sugarcane fiber, 8 parts of PPC, 8 parts of PGA and 6.5 parts of hollow glass microspheres, 0.3 parts of dimethyldiallylammonium chloride (DMDAAC), 0.45 parts of dihydroxymethylpropionic acid (DMPA), 0.75 parts of BASF ADR 4400, 1.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.4 parts of nano ZnO, 0.6 parts of nano CeO2, 0.3 parts of anti-hydrolysis agent HYY-003, 0.7 parts of bis (2,6-diisopropylbenzene) carbodiimide, 1.25 parts of antioxidant S-9228, 0.75 parts of calcium stearate, and 0.5 parts of nano cellulose are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is adopted, and the air supply temperature is 18-65°C to obtain granules special for the filling layer;
[0223] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0224] C1: 36 parts of PHB, 20 parts of P34HB (4HB content is 8 mol%), 12 parts of PHBHHx (3HHx content is 20 mol%), 6 parts of sugarcane fiber, 8 parts of PPC, 8 parts of PGA and 0.4 parts of dimethyldiallyl ammonium chloride (DMDAAC), 0.6 parts of dihydroxymethylpropionic acid (DMPA), 1 part of BASF ADR 4400, 4.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.3 parts of nano ZnO, 0.45 parts of nano CeO2, 0.3 parts of anti-hydrolysis agent HYY-003, 0.7 parts of bis (2,6-diisopropylbenzene) carbodiimide, 1 part of antioxidant S-9228, 0.75 parts of calcium stearate, 0.5 parts of nano cellulose, 1.5 parts of azodicarbonamide, 1.2 parts of foaming agent SP1000C, 0.8 parts of ammonium bicarbonate were mixed and dried, and injected into a double screw with a heating device. The rod extruder is plasticized and formed into a film by calendering, which is the foaming layer. It is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are mainly made of the same material, no adhesive is required. Then it is sent to a foaming furnace for foaming. The plasticizing temperature is 120-195℃, the preheating temperature is 65-105℃, the foaming temperature is 45-100℃, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0225] D1: By mass, 18 parts of PHB, 10 parts of P34HB (4HB content is 8 mol%), 6 parts of PHBHHx (3HHx content is 20 mol%), 3 parts of sugarcane fiber, 4 parts of PPC, 4 parts of PGA and 0.75 parts of hollow glass microspheres, 0.2 parts of dimethyldiallyl ammonium chloride (DMDAAC), 0.3 parts of dihydroxymethylpropionic acid (DMPA), 0.5 parts of BASF ADR 4400, 1 part of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.2 parts of nano ZnO, 0.3 parts of nano CeO2, 0.15 parts of anti-hydrolysis agent HYY-003, 0.35 parts of bis (2,6-diisopropylbenzene) carbodiimide, 0.5 parts of antioxidant S-9228, 0.45 parts of calcium stearate, and 0.3 parts of nano cellulose are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is adopted, and the air supply temperature is 18-65°C to obtain granules special for the simulation layer;
[0226] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0227] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0228] The test results of the properties of the obtained artificial leather are shown in Table 5 below. Figure 1 .
[0229] Table 5 Test data of PHB / P34HB / PHBHHx+sugarcane fiber+PPC+PGA composite artificial leather
[0230]
[0231]
[0232] Example 4: PHBV / P34HB / PHBHHx+soy protein fiber+bamboo fiber+PBS composite artificial leather A1: By mass, weigh 24 parts of PHBV (3HV content is 5 mol%), 12 parts of P34HB (4HB content is 10 mol%), 12 parts of PHBHHx (3HHx content is 8 mol%), 3 parts of soybean protein fiber, 6 parts of bamboo fiber, 10.5 parts of PBS and 4 parts of mica powder, 0.4 parts of dimethyldiallyl ammonium chloride (DMDAAC), 0.2 parts of 1,4-butanediol, 0.4 parts of BASF ADR 4468, 1 part of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.4 part of nano ZnO, 0.6 part of rutile TiO2, 0.45 part of bis(2,6-diisopropylbenzene)carbodiimide, 0.3 part of anti-hydrolysis agent HD900A, 1 part of antioxidant 2777, 0.5 part of zinc stearate, 0.75 part of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is used, and the air supply temperature is 18-65°C to obtain fiber-specific granules;
[0233] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0234] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0235] B1: By mass, weigh 32 parts of PHBV (3HV content is 5 mol%), 16 parts of P34HB (4HB content is 10 mol%), 16 parts of PHBHHx (3HHx content is 8 mol%), 4 parts of soybean protein fiber, 8 parts of bamboo fiber, 14 parts of PBS and 6.5 parts of mica powder, 0.6 parts of dimethyldiallyl ammonium chloride (DMDAAC), 0.3 parts of 1,4-butanediol, 0.6 parts of BASF ADR4468, 1.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 0.6 parts of bis(2,6-diisopropylbenzene)carbodiimide, 0.4 parts of anti-hydrolysis agent HD900A, 1.25 parts of antioxidant 2777, 0.5 parts of zinc stearate, and 0.75 parts of fumed nano silicon dioxide are mixed, melted and cooled to granulate by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is used, and the air supply temperature is 18-65°C to obtain a special granular material for the filling layer;
[0236] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0237] C1: By mass, weigh 32 parts of PHBV (3HV content is 5 mol%), 16 parts of P34HB (4HB content is 10 mol%), 16 parts of PHBHHx (3HHx content is 8 mol%), 4 parts of soy protein fiber, 8 parts of bamboo fiber, 14 parts of PBS and 0.8 parts of dimethyldiallylammonium chloride (DMDAAC), 0.4 parts of 1,4-butanediol, 0.8 parts of BASF ADR 4468, 4.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.3 parts of nano ZnO, 0.45 parts of rutile TiO2, 0.6 parts of bis(2,6-diisopropylbenzene)carbodiimide, 0.4 parts of anti-hydrolysis agent HD900A, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica, 1.5 parts of azodicarbonamide, 0.8 parts of leather foaming agent HF-800, 1.2 parts of sodium bicarbonate were mixed and dried, and injected into a heating device. The twin-screw extruder plasticizes and forms a film through calendering, which is the foaming layer. The foaming layer is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are made of the same main material, no adhesive is required. Then it is sent to a foaming furnace for foaming. The plasticizing temperature is 120-195°C, the preheating temperature is 65-105°C, the foaming temperature is 45-100°C, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm. D1: By mass, weigh 16 parts of PHBV (3HV content is 5 mol%), 8 parts of P34HB (4HB content is 10 mol%), 8 parts of PHBHHx (3HHx content is 8 mol%), 2 parts of soy protein fiber, 4 parts of bamboo fiber, 7 parts of PBS and 0.75 parts of mica powder, 0.4 parts of dimethyldiallylammonium chloride (DMDAAC), 0.2 parts of 1,4-butanediol, 0.4 parts of BASF ADR 4468, 1 part of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, 0.2 part of nano ZnO, 0.3 part of rutile TiO2, 0.3 part of bis(2,6-diisopropylbenzene)carbodiimide, 0.2 part of anti-hydrolysis agent HD900A, 0.5 part of antioxidant 2777, 0.25 part of zinc stearate, 0.5 part of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is adopted, and the air supply temperature is 18-65°C, to obtain granules special for the simulation layer;
[0238] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0239] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0240] The test results of the properties of the obtained artificial leather are shown in Table 6 below. Figure 1 .
[0241] Table 6 Test data of PHBV / P34HB / PHBHHx+soy protein fiber+bamboo fiber+PBS composite artificial leather
[0242]
[0243]
[0244] Example 5: PHB / P34HB+black tea fiber+bamboo fiber+PGA composite artificial leather
[0245] A1: 30 parts of PHB, 24 parts of P34HB (4HB content is 15 mol%), 4.5 parts of black tea fiber, 4 parts of bamboo fiber, 5 parts of PGA and 4 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 0.75 parts of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205°C, annular blowing was used, and the air supply temperature was 18-65°C to obtain fiber-specific granules;
[0246] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0247] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0248] B1: by weight, 40 parts of PHB, 32 parts of P34HB (4HB content is 15 mol%), 6 parts of black tea fiber, 5.3 parts of bamboo fiber, 6.7 parts of PGA and 6.5 parts of mica powder, 0.45 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.45 parts of dihydroxymethyl propionic acid (DMPA), 0.6 parts of BASF ADR 4400, 1.5 parts of acetyl citrate tributyl ester, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1.25 parts of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205 ° C, annular blowing was adopted, and the air supply temperature was 18-65 ° C to obtain a special granular material for the filling layer;
[0249] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0250] C1: In terms of mass, 40 parts of PHB, 32 parts of P34HB (4HB content is 15 mol%), 6 parts of black tea fiber, 5.3 parts of bamboo fiber, 6.7 parts of PGA, 0.6 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.6 parts of dihydroxymethyl propionic acid (DMPA), 0.8 parts of BASF ADR 4400, 4.5 parts of acetyl tributyl citrate, 0.3 parts of nano ZnO, 0.45 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica, 1.5 parts of azodicarbonamide, 0.8 parts of leather foaming agent HF-800, and 1.2 parts of sodium bicarbonate were mixed and dried, injected into a twin-screw extruder with a heating device for plastication, and formed into a film by calendering. The foaming layer is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are made of the same main material, no adhesive is required. Then it is sent to a foaming furnace for foaming, wherein the plasticizing temperature is 120-195°C, the pre-heating temperature is 65-105°C, the foaming temperature is 45-100°C, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0251] D1: by mass, 20 parts of PHB, 16 parts of P34HB (4HB content is 15 mol%), 3 parts of black tea fiber, 2.7 parts of bamboo fiber, 3.3 parts of PGA and 0.75 parts of mica powder, 0.3 parts of N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonic acid sodium, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.2 parts of nano ZnO, 0.3 parts of rutile TiO2, 0.5 parts of anti-hydrolysis agent HYY-003, 0.5 parts of antioxidant 2777, 0.25 parts of zinc stearate, 0.5 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to granulate, wherein the barrel temperature was set to 160-205 ° C, annular blowing was used, and the air supply temperature was 18-65 ° C to obtain a special granular material for the simulation layer;
[0252] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0253] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0254] The test results of the properties of the obtained artificial leather are shown in Table 7 below. Figure 1 .
[0255] Table 7 Test data of PHB / P34HB+black tea fiber+bamboo fiber+PGA composite artificial leather
[0256]
[0257]
[0258] Example 6: PHB / P34HB+mulberry fiber+bamboo fiber+PBAT composite artificial leather
[0259] A1: 34 parts of PHB, 16 parts of P34HB (4HB content is 20 mol%), 4.5 parts of mulberry fiber, 2.5 parts of bamboo fiber, 10.5 parts of PBAT and 4 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 0.75 parts of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205°C, annular blowing was used, and the air supply temperature was 18-65°C to obtain fiber-specific granules;
[0260] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0261] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0262] B1: By mass, weigh 45.3 parts of PHB, 21.3 parts of P34HB (4HB content is 20 mol%), 6 parts of mulberry fiber, 3.4 parts of bamboo fiber, 14 parts of PBAT and 6.5 parts of mica powder, 0.45 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.45 parts of dihydroxymethyl propionic acid (DMPA), 0.6 parts of BASF ADR 4400, 1.5 parts of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1.25 parts of antioxidant 2777, 0.5 parts of zinc stearate, and 0.75 parts of fumed nano silicon dioxide are mixed, melted and cooled into granules by a twin-screw extruder, wherein the barrel temperature is set to 160-205°C, annular blowing is adopted, and the air supply temperature is 18-65°C, to obtain granules specially used for the filling layer;
[0263] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0264] C1: In terms of mass fractions, 45.3 parts of PHB, 21.3 parts of P34HB (4HB content is 20 mol%), 6 parts of mulberry fiber, 3.4 parts of bamboo fiber, 14 parts of PBAT, 0.6 parts of sodium N, N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, 0.6 parts of dihydroxymethylpropionic acid (DMPA), 0.8 parts of BASF ADR 4400, 4.5 parts of acetyl tributyl citrate, 0.3 parts of nano ZnO, 0.45 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica, 1.5 parts of azodicarbonamide, 0.8 parts of leather foaming agent HF-800, and 1.2 parts of sodium bicarbonate were weighed, mixed and dried, injected into a twin-screw extruder with a heating device for plastication, and formed into a film by calendaring. The foaming layer is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are made of the same main material, no adhesive is required. Then it is sent to a foaming furnace for foaming, wherein the plasticizing temperature is 120-195°C, the pre-heating temperature is 65-105°C, the foaming temperature is 45-100°C, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0265] D1: 22.6 parts of PHB, 10.7 parts of P34HB (4HB content is 20 mol%), 3 parts of mulberry fiber, 1.7 parts of bamboo fiber, 7 parts of PBAT and 0.75 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.2 parts of nano ZnO, 0.3 parts of rutile TiO2, 0.5 parts of anti-hydrolysis agent HYY-003, 0.5 parts of antioxidant 2777, 0.25 parts of zinc stearate, 0.5 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205 ° C, annular blowing was used, and the air supply temperature was 18-65 ° C to obtain granules for the simulation layer;
[0266] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0267] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0268] The test results of the properties of the obtained artificial leather are shown in Table 8 below. Figure 1 .
[0269] Table 8 Test data of PHB / P34HB+mulberry fiber+bamboo fiber+PBAT composite artificial leather
[0270]
[0271]
[0272] Example 7: PHB / P34HB+black tea fiber+soy protein fiber+PBAT composite artificial leather
[0273] A1: 33 parts of PHB, 15 parts of P34HB (4HB content is 24 mol%), 6 parts of black tea fiber, 6 parts of soybean protein fiber, 7.5 parts of PBAT and 4 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 0.75 parts of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205°C, annular blowing was used, and the air supply temperature was 18-65°C to obtain fiber-specific granules;
[0274] A2: The fiber-specific pellets are vacuum dried, injected into an extrusion device with a heating device to melt, and then melted and extruded through a screw. Different spinnerets, spinning processes, and subsequent drafting and winding or spunlace, needle punching and other fiber web reinforcement molding processes are used to obtain PHA filaments or PHA non-woven fabrics. The weight of PHA non-woven fabrics is 30-400g / m 2 between;
[0275] A3: The PHA filament obtained in A2 is unwound and knitted or woven to obtain a gram weight of 30-400g / m 2 The PHA base fabric between, the PHA base fabric or the PHA non-woven fabric obtained by A2 are all PHA base fabric layers.
[0276] B1: by weight, 44 parts of PHB, 20 parts of P34HB (4HB content is 24 mol%), 8 parts of black tea fiber, 8 parts of soybean protein fiber, 10 parts of PBAT and 6.5 parts of mica powder, 0.45 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.45 parts of dihydroxymethyl propionic acid (DMPA), 0.6 parts of BASF ADR 4400, 1.5 parts of acetyl tributyl citrate, 0.4 parts of nano ZnO, 0.6 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1.25 parts of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to form granules, wherein the barrel temperature was set to 160-205°C, annular blowing was used, and the air supply temperature was 18-65°C to obtain granules for the filling layer;
[0277] B2: The special pellets for the filling layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the filling layer. The film is then tightly compounded with the pre-heated PHA base fabric layer by a three-roller setting machine. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105°C, the casting temperature is 160-205°C, and the casting film thickness is 70-700μm.
[0278] C1: In terms of mass, 44 parts of PHB, 20 parts of P34HB (4HB content is 24 mol%), 8 parts of black tea fiber, 8 parts of soybean protein fiber, 10 parts of PBAT and 0.6 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.6 parts of dihydroxymethyl propionic acid (DMPA), 0.8 parts of BASF ADR 4400, 4.5 parts of acetyl tributyl citrate, 0.3 parts of nano ZnO, 0.45 parts of rutile TiO2, 1 part of anti-hydrolysis agent HYY-003, 1 part of antioxidant 2777, 0.5 parts of zinc stearate, 0.75 parts of fumed nano silica, 1.5 parts of azodicarbonamide, 0.8 parts of leather foaming agent HF-800, and 1.2 parts of sodium bicarbonate were mixed and dried, injected into a twin-screw extruder with a heating device for plastication, and formed into a film by calendaring. The foaming layer is tightly compounded with the pre-heated PHA base cloth / filling layer through a three-roller shaping machine. The foaming layer is close to the filling layer. Since the two layers are made of the same main material, no adhesive is required. Then it is sent to a foaming furnace for foaming, wherein the plasticizing temperature is 120-195°C, the pre-heating temperature is 65-105°C, the foaming temperature is 45-100°C, the foaming time is 15-30min, and the final thickness of the foaming layer after expansion and cooling is 280-3000μm.
[0279] D1: by mass, 22 parts of PHB, 10 parts of P34HB (4HB content is 24 mol%), 4 parts of black tea fiber, 4 parts of soybean protein fiber, 5 parts of PBAT and 0.75 parts of mica powder, 0.3 parts of sodium N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonate, 0.3 parts of dihydroxymethyl propionic acid (DMPA), 0.4 parts of BASF ADR 4400, 1 part of acetyl tributyl citrate, 0.2 parts of nano ZnO, 0.3 parts of rutile TiO2, 0.5 parts of anti-hydrolysis agent HYY-003, 0.5 parts of antioxidant 2777, 0.25 parts of zinc stearate, 0.5 parts of fumed nano silica were mixed, melted and cooled by a twin-screw extruder to granulate, wherein the barrel temperature was set to 160-205 ° C, annular blowing was used, and the air supply temperature was 18-65 ° C to obtain special granules for the simulation layer;
[0280] D2: The special pellets for the simulation layer are vacuum dried, injected into a twin-screw extruder with a heating device to melt, and formed into a film by casting to form the simulation layer. The simulation layer is tightly compounded with the pre-heated PHA base cloth / filling / foaming layer by a three-roller setting machine. The simulation layer is close to the foaming layer. Since the two layers are mainly made of the same material, no adhesive is required. The pre-heating temperature is controlled to be 65-105℃, the casting temperature is 150-215℃, and the casting film thickness is 35-420μm.
[0281] D3: One side of the simulation layer is embossed by a method such as flat plate embossing or roller embossing and then cooled to obtain a simulation texture, and then dyed and rolled to obtain PHA artificial leather.
[0282] The test results of the properties of the obtained artificial leather are shown in Table 9 below. Figure 1 .
[0283] Table 9 Test data of PHB / P34HB+black tea fiber+soy protein fiber+PBAT composite artificial leather
[0284]
[0285]
[0286] Comparative Example 1: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather with excessive addition of P34HB Compared with Example 1, the addition of P34HB is too high, and the addition of PHB is reduced accordingly.
[0287] Among them, A1 contains 10 parts of PHB and 40 parts of P34HB (4HB content is 16 mol%); B1 contains 13.3 parts of PHB and 53.4 parts of P34HB (4HB content is 16 mol%); C1 contains 13.3 parts of PHB and 53.4 parts of P34HB (4HB content is 16 mol%); D1 contains 6.7 parts of PHB and 26.6 parts of P34HB (4HB content is 16 mol%); the mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0288] Because the amount of P34HB added in Control Example 1 is too high, the expansion coefficient (15.6), sound insulation (24.5dB), tensile load (warp: 403; weft: 311), tear load (warp: 16.2; weft: 15.8), peel load (warp: 17.4; weft: 17.2) and waterproofness (grade 4) of the prepared artificial leather are worse than those in Example 1.
[0289] Comparative Example 2: PHB with too low P34HB addition / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather Compared with Example 1, the addition of P34HB is too low, and the addition of PHB is increased accordingly.
[0290] Among them, A1 contains 40 parts of PHB and 10 parts of P34HB (4HB content is 16 mol%); B1 contains 53.4 parts of PHB and 13.3 parts of P34HB (4HB content is 16 mol%); C1 contains 53.4 parts of PHB and 13.3 parts of P34HB (4HB content is 16 mol%); D1 contains 26.7 parts of PHB and 6.6 parts of P34HB (4HB content is 16 mol%); the mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0291] Since the amount of P34HB added in Control Example 2 is too low, the softness (grade 4.1), expansion coefficient (17.6), sound insulation (25.3), elongation at break (warp: 5.7; weft: 5.6), surface color fastness (grade 4), dyeing uniformity (grade 4) and folding fastness (cracks on the surface after 30,000 times) of the prepared artificial leather are worse than those in Example 1.
[0292] Comparative Example 3: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather without preheating process Compared with Example 1, no preheating process is required and the composite is directly composited. The mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0293] Since the method described in Comparative Example 3 does not have a preheating step, the peeling load (warp: 13.8; weft: 12.4) and water resistance (grade 4) of the artificial leather prepared therefrom are inferior to those of Example 1.
[0294] Comparative Example 4: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather without filling layer Compared with Example 1, there is no PHA filling layer. The mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0295] Since the artificial leather prepared in Control Example 4 has no filling layer, the sound insulation (24.8), tensile load (warp: 246; weft: 235), tear load (warp: 153; weft: 148), peel load (warp: 139; weft: 132), light resistance (level 4), and water resistance (level 2) of the artificial leather prepared therefrom are all worse than those in Example 1.
[0296] Comparative Example 5: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather with too low 4HB molar content Compared with Example 1, the molar content of 4HB in P34HB is too low, and the content of 4HB is 1 mol%. The mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0297] Since the molar content of 4HB in P34HB in Control Example 5 is too low, the softness (3.9), expansion coefficient (15.4), sound insulation (26.7), elongation at break (warp: 4.5; weft: 5.2), surface color fastness (grade 4), and folding fastness (cracks on the surface after 20,000 times) of the artificial leather prepared therefrom are worse than those in Example 1.
[0298] Comparative Example 6: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather with excessively high 4HB molar content Compared with Example 1, the 4HB molar content in P34HB is too high, and the 4HB content is 35 mol%. The mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0299] Since the molar content of 4HB in P34HB in Control Example 6 is too high, the expansion coefficient (5.1), sound insulation (17.7), tensile load (warp: 389; weft: 292), tear load (warp: 154; weft: 153), peel load (warp: 16.1; weft: 15.7), and waterproofness (4 levels) of the artificial leather prepared therefrom are inferior to those in Example 1.
[0300] Comparative Example 7: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather without filler Compared with Example 1, no filler was added. The mass fractions of other substances and the parameters in the processing process were the same as those in Example 1.
[0301] Since no filler was added in Control Example 7, the sound insulation (18.3) of the artificial leather prepared therefrom was worse than that in Example 1. Control Example 8: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather without adding ultraviolet absorber Compared with Example 1, no ultraviolet absorber was added. The mass fractions of other substances and the parameters in the processing process were the same as those in Example 1.
[0302] Since no ultraviolet absorber was added in Control Example 8, the sound insulation (22.7) and light resistance (grade 2) of the artificial leather prepared therefrom were inferior to those in Example 1.
[0303] Comparative Example 9: PHB / P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather without filler and UV absorber Compared with Example 1, no filler and UV absorber were added. The mass fractions of other substances and the parameters in the processing process were the same as those in Example 1.
[0304] Since the control example 9 does not add filler and ultraviolet absorber, the sound insulation (14.3) and light resistance (grade 2) of the artificial leather prepared therefrom are inferior to those of the embodiment 1.
[0305] Control Example 10: PLA / PBAT+black tea fiber+mulberry fiber+PBS composite artificial leather without PHA added Compared with Example 1, PHA was not used, PHB in Example 1 was replaced by PLA, P34HB was replaced by PBAT, and the mass fractions of other substances and parameters in the processing process were the same as those in Example 1.
[0306] Since PHA is not added in Control Example 10, the expansion coefficient (6.8), sound insulation (18.2), peeling load (warp: 20.5; weft: 19.7), surface color fastness (grade 3), dyeing uniformity (grade 2), light fastness (grade 4), folding fastness (cracks on the surface after 30,000 times), and water resistance (grade 3) of the artificial leather prepared therefrom are worse than those in Example 1.
[0307] Comparative Example 11: P34HB+black tea fiber+mulberry fiber+PBS composite artificial leather with only P34HB and 4HB in moderate proportion
[0308] Compared with Example 1, only P34HB was added, and PHB was not added.
[0309] Among them, the P34HB (4HB content is 16 mol%) in A1 is 50 parts; the P34HB (4HB content is 16 mol%) in B1 is 66.7 parts; the P34HB (4HB content is 16 mol%) in C1 is 66.7 parts; the P34HB (4HB content is 16 mol%) in D1 is 33.3 parts; PHB is not added in each step, and the mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0310] Since only P34HB was added to the control example 11, the expansion coefficient (12.9), sound insulation (20.3), tensile load (warp: 350; weft: 262), tear load (warp: 14.3; weft: 13.0), peel load (warp: 15.4; weft: 14.1) and waterproofness (grade 3) of the artificial leather prepared therefrom are worse than those in Example 1.
[0311] Comparative Example 12: PHB+black tea fiber+mulberry fiber+PBS composite artificial leather without adding P34HB Compared with Example 1, no P34HB is added, and only PHB is added.
[0312] Among them, the PHB content in A1 is 50 parts; the PHB content in B1 is 66.7 parts; the PHB content in C1 is 66.7 parts; the PHB content in D1 is 33.3 parts; P34HB is not added in each step, and the mass fractions of other substances and the parameters in the processing process are the same as those in Example 1.
[0313] Since P34HB is not added in Control Example 12, the softness (grade 3.2), expansion coefficient (9.8), sound insulation (11.4), elongation at break (warp: 3.0; weft: 2.7), peeling load (warp: 12.9; weft: 12.6), surface color fastness (grade 3), dyeing uniformity (grade 4) and folding fastness (cracks on the surface after 10,000 times) of the artificial leather prepared therefrom are worse than those in Example 1.
[0314] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An artificial leather, characterized in that: The artificial leather comprises a base fabric layer, a filling layer, a foaming layer and a simulation layer, and the raw materials of the base fabric layer, the filling layer, the foaming layer and the simulation layer comprise a substrate, and the substrate comprises a PHA substrate; The PHA substrate is a mixed raw material of P34HB and non-P34HB PHA; The added mass of P34HB in the PHA substrate is 21%-79%; The molar content of 4HB in the P34HB is 3%-30%.
2. The artificial leather according to claim 1, characterized in that The non-P34HB PHA includes one or more of P(HB-LA), P3HP, PHB, P4HB, PHV, PHO, PHN, PHD, PHBV, PHBHHp, PHBHHx, P3HB4HB3HV or P3HB4HB5HV.
3. The artificial leather according to claim 1, characterized in that: The substrate also includes a non-PHA substrate, and the mass ratio of the PHA substrate to the non-PHA substrate is (1-5):
1.
4. The artificial leather according to claim 3, characterized in that: The non-PHA substrate includes one or more of PLA, PBAT, PPC, PBS, PGA, black tea fiber, soybean protein fiber, mulberry fiber, sugarcane fiber or bamboo fiber.
5. The artificial leather according to claim 1, characterized in that: The artificial leather further comprises auxiliary materials, and the auxiliary materials include one or both of fillers and / or ultraviolet absorbers.
6. The artificial leather according to claim 5, characterized in that The filler is a micron-sized filler, and the ultraviolet absorber is a nano-sized inorganic powder.
7. The artificial leather according to claim 5, characterized in that: The auxiliary materials also include one or more of a chain extender, an environmentally friendly plasticizer, an anti-hydrolysis agent, an antioxidant, a heat stabilizer or a foaming agent.
8. The artificial leather according to claim 5, characterized in that: The filler includes one or more of hollow glass microspheres, mica powder or talc powder.
9. The artificial leather according to claim 5, characterized in that: The ultraviolet absorber includes one or more of nano ZnO, rutile TiO2 or nano CeO2.
10. The artificial leather according to claim 7, characterized in that: The chain extender includes one or more of sodium N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonate, dimethylolpropionic acid, dimethyldiallylammonium chloride, 1,4-butanediol, BASF ADR 4400 or BASF ADR 4468.
11. The artificial leather according to claim 7, characterized in that: The environmentally friendly plasticizer includes one or both of acetyl tributyl citrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate.
12. The artificial leather according to claim 7, characterized in that: The anti-hydrolysis agent includes one or more of the anti-hydrolysis agent HYY-003, bis(2,6-diisopropylbenzene)carbodiimide or anti-hydrolysis agent HD900A.
13. The artificial leather according to claim 7, characterized in that: The antioxidant includes one or more of antioxidant 2777, tris(2,4-di-tert-butylphenyl)phosphite or antioxidant S-9228.
14. The artificial leather according to claim 7, characterized in that: The heat stabilizer includes one or more of stearate, nanocellulose or fumed nanosilica.
15. The artificial leather according to claim 7, characterized in that: The foaming agent includes one or more of azodicarbonamide, foaming agent SP1000C, leather foaming agent HF-800, sodium bicarbonate or ammonium bicarbonate.
16. The artificial leather according to claim 1, characterized in that The innermost layer of the artificial leather is a base fabric layer, the outer side of the base fabric layer is a filling layer, the outer side of the filling layer is a foaming layer, and the outermost layer is a simulation layer.
17. The artificial leather according to claim 5, characterized in that: In the base fabric layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (3-7): (1-3):
1.
18. The artificial leather according to claim 5, characterized in that In the filling layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (2-6): (1-3):
1.
19. The artificial leather according to claim 5, characterized in that: In the foaming layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (2-6): (1-3):
1.
20. The artificial leather according to claim 5, characterized in that In the simulation layer, the mass ratio of the PHA substrate, the non-PHA substrate and the auxiliary material is (4-10): (1-3):
1.
21. A method for preparing the artificial leather according to any one of claims 1 to 20, characterized in that: The preparation method comprises preparing a base fabric layer, a filling layer, a foaming layer and a simulation layer, and then stacking and compounding them to prepare artificial leather.
22. The preparation method according to claim 21, characterized in that: The compounding includes heating.
23. The preparation method according to claim 22, characterized in that: The heating temperature is 50-150°C.
24. The preparation method according to claim 21, characterized in that: The method for preparing the base fabric layer comprises: A1: Mix the raw materials, melt them, cool them and granulate them to obtain fiber-specific granules; A2: melt-extrude the fiber-specific pellets, obtain filaments or non-woven fabrics through a molding process, and obtain a base fabric layer. The step A2 also includes unwinding the filaments and obtaining the base fabric through a knitting or weaving process.
25. The preparation method according to claim 21, characterized in that: The preparation of the filling layer comprises: B1: Mix the raw materials, melt them, cool them and granulate them to obtain granules for the filling layer; B2: The pellets specially used for the filling layer are melted and then cast into a film to obtain the filling layer.
26. The preparation method according to claim 21, characterized in that: The preparation of the foaming layer comprises: C1: The raw materials are mixed, plasticized, calendered into a film, and then heated and foamed to obtain a foamed layer.
27. The preparation method according to claim 21, characterized in that: The preparation of the simulation layer comprises: D1: Mix the raw materials, melt them, cool them and granulate them to obtain granules for the simulation layer; D2: The special pellets for the simulation layer are melted and cast into a film to obtain the simulation layer.
28. Use of the artificial leather according to any one of claims 1 to 20 or the artificial leather prepared by the preparation method according to any one of claims 21 to 27, characterized in that: The application includes application in manufacturing leather products, simulated skin or antibacterial wound dressings; the leather products include one or more of automobile interior decoration, leather furniture, leather shoes or leather clothes.
Citation Information
Patent Citations
Dry-process artifical leather manufacturing machine
WO2012065372A1
Composition and method for production of a highly flexible PHA sheet
WO2022173465A1